Synergistic antibacterial effect and mechanism of high hydrostatic pressure and mannosylerythritol Lipid-A on Listeria monocytogenes. (May 2022) - Liu, Xiayu; Zhang, Leyi; Pang, Xinxin; Wu, Yansha; Wu, Yajing; Shu, Qin; Chen, Qihe; Zhang, Xinglin
Abstract: Listeria monocytogenes is an important food-borne pathogen that can cause fatal listeriosis. High hydrostatic pressure (HHP) in combination with antimicrobial agent is a potential antibacterial strategy for controlling L. monocytogenes in the food industry. The aim of this study was to investigate the antibacterial effect and the underlying mechanisms of HHP alone and HHP in combination with Mannosylerythritol Lipid-A (MEL-A), an antimicrobial biosurfatant, on L. monocytogenes . The results of antibacterial rate and morphological changes showed that a combined HHP (100, 200, 300 MPa) and MEL-A (16 μg/mL, 32 μg/mL) treatment had a synergistic bactericidal effect on L. monocytogenes . The synergistic treatment caused severe damage to the cell membrane structure of L. monocytogenes . To further explore the antibacterial mechanism of the synergistic treatment of HHP and MEL-A on L. monocytogenes, genome-wide transcriptome analysis was carried out and identified 1392 differentially expressed genes (DEGs). Enrichment analysis of the DEGs showed that HHP induced significant down-expression of membrane-related genes and up-regulation of ribosome-related pathways (50 S and 30 S ribosomal proteins). Interestingly, ribosome was also the most significantly enriched pathway in the synergistic treatment group. Moreover, compared to HHP treatment alone, synergistic treatment also affected pathways related to the PTS system. In addition, the good safety performance in vivo and in vitro indicates that MEL-A could be potentially used as a potential additive for controlling L. monocytogenes in the food industry. This study reveals the synergistic bactericidal effect and mechanisms of a combined HHP and MEL-A treatment against L. monocytogenes, which may provide potential strategies for prevention and control of food-borne pathogens. Highlights: High hydrostatic pressure (HHP) and mannosylerythritol lipids-A (MEL-A) exhibited synergistic bactericidal effect. Severe damage in cell membrane structure were observed by SEM and TEM. Ribosome related pathways were significantly enhanced in both HHP and MH treatment groups. In vitro and in vivo safety assessment experiments revealed the safety of MEL-A.